KARAKTERISTIK PASIEN TRIGGER FINGER DI RSUD ABDOEL WAHAB SJAHRANIE TAHUN 2018 – 2023 (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Trigger finger is a condition characterized by inflammation of the flexor tendon and its surrounding sheath, resulting in irregular movement of the tendon inside the sheath. Inflammation can lead to an abrupt and irregular movement, causing a clicking sound when the finger is forcefully stretched and then flexed. The lack of studies conducted in Indonesia on the characteristics of patients with trigger finger served as a reason for the author's decision to choose this research problem. The aim of this study was to find the specific characteristics of trigger finger patients at Abdoel Wahab Sjahranie Regional Public Hospital, including their gender, age, comorbidities, affected hand, affected finger, grading, and treatment. This study employed an observational descriptive design using a cross-sectional method. The data were collected from medical records using a complete sampling method, which included 49 patients diagnosed with trigger finger between 2019 and 2023. The findings indicated that the largest proportion of individuals with trigger finger were 52 years old (10.2%), mostly female (69.4%), and a substantial number had comorbidities (65.3%). The right hand was the most significantly affected hand, accounting for 42.9% of cases, whereas the right third finger was the most commonly affected finger, representing 30.6% of cases.Patients most frequently suffered grade I (38.8%) grading, and the most prevalent treatment they underwent was surgery (55.1%).